Developing a Predictive Model of Organizational Learning Based on Multiple Intelligences: A Case Study of Iranian Schools - Ghahri, Aref; Kargar Shahamat, Bahman; Roohi Issa Lou, Mohammad (Future of Work and Digital Management Journal, 2026)
This study aimed to develop and validate a predictive model of organizational learning based on Gardner’s multiple intelligences theory in Iranian schools, emphasizing the roles of leadership, capacity building, and enabling learning environments in fostering sustainable educational development. The study employed a mixed-methods design with an exploratory–sequential approach. In the qualitative phase, 125 scholarly works were reviewed systematically through a meta-synthesis process, of which 20 met inclusion criteria after CASP quality screening. Thematic analysis of these sources and semi-structured interviews with educators led to the identification of 80 basic codes, 16 organizing themes, and 3 overarching dimensions—enabling learning environment, capacity building, and educational leadership based on multiple intelligences. In the quantitative phase, a researcher-made questionnaire was developed from the qualitative findings and distributed among 355 teachers selected through random sampling. Data were analyzed using Structural Equation Modeling (SEM) with SmartPLS version 3 to test measurement and structural models. Inferential analysis revealed strong relationships among the core constructs, with R² values between 0.868 and 0.944 and Q² indices ranging from 0.285 to 0.387, confirming the model’s high explanatory and predictive power. The Fornell–Larcker criterion validated discriminant reliability among dimensions. Results showed that educational leadership based on multiple intelligences significantly predicted organizational learning, while capacity building and an enabling learning environment mediated this effect. Emotional intelligence, reflective learning, and participatory culture were identified as key mechanisms linking leadership to sustainable organizational learning. The study confirmed that integrating multiple intelligences into educational leadership and institutional processes enhances organizational learning, adaptability, and innovation. The validated model provides a theoretical and practical framework for promoting sustainable learning organizations in schools.